A Survey of the Languages Spoken by the Students at UPNG : E.R.U. Report 13 - Liefrink, Frans (University of Papua New Guinea, 1974)
A compiled report of a survey that was carried out on the number of students who spoke English, pidgin, Hiri Motu or other mother tongues as well as how often these languages are spoken from primary school up to tertiary institution at The University of Papua New Guinea as part of a pidgin language studies in 1974.